2018
DOI: 10.1088/1674-4527/18/9/105
|View full text |Cite
|
Sign up to set email alerts
|

Local sunspot oscillations and umbral dots

Abstract: Data analysis of sunspot oscillation based on 6-hr SDO run of observation showed that low frequency (0.2 < ω < 1mHz) oscillations are local similar to three and five minute oscillations. The oscillations in the sunspot are concentrated in cells of a few arcsec, each of which has its own oscillation spectrum. The analysis of two scenario for sunspot oscillations leads to conclusion that local sunspot oscillations occur due to subphotospheric resonator for slow mhd waves. Empirical models of sunspot atmosphere a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…We see from figure 2d that the spectrum consists of a series of narrowband peaks (thin lines) covering the period range 2.0-3.5 min. The fine structure of spectrum as width between peaks does not exceed approximately 0.1 mHz, which is consistent with previously obtained results [45] sources inside the umbra. It can be assumed [9] that each source is associated with a separate harmonic of the spectrum.…”
Section: Results and Discussion (A) Temporal Dynamics Of The 3-min Brsupporting
confidence: 92%
“…We see from figure 2d that the spectrum consists of a series of narrowband peaks (thin lines) covering the period range 2.0-3.5 min. The fine structure of spectrum as width between peaks does not exceed approximately 0.1 mHz, which is consistent with previously obtained results [45] sources inside the umbra. It can be assumed [9] that each source is associated with a separate harmonic of the spectrum.…”
Section: Results and Discussion (A) Temporal Dynamics Of The 3-min Brsupporting
confidence: 92%
“…In the photosphere, weak 3-min oscillations are not visible against powerful 5-min oscillations. However, the 3-min oscillations localized in small areas appeared to be visible as a spatial resolution of the observational instrument was increased (Jess et al 2012;Zhugzhda & Sych 2014;Krishna Prasad et al 2015;Chae et al 2017;Zhugzhda & Sych 2018). The obtained umbral oscillations show the different spatial and spectral localization depending on height.…”
Section: Spatial Distribution and Dynamics Of Oscillationsmentioning
confidence: 91%
“…An alternative mechanism revolves around the creation of a resonance cavity in the the solar atmosphere, which has recently been shown to exist by Jess et al (2020), and independently confirmed by Felipe et al (2020). Other localized waves can be also excited due to residual convection in the umbra (Zhugzhda & Sych 2018).…”
Section: Introductionmentioning
confidence: 92%